Pengaruh Penambahan Kompos Limbah Lumpur Kertas Dan Sekam Padi Pada Media Tanam Terhadap Pertumbuhan Dan Hasil Tanaman Bayam Merah (Amaranthus Gangeticus L) Varietas Mira - Rizqi Fajar Shidiq; Muharam Muharam; Sulistyo Sidik Purnomo (Jurnal Ilmiah Wahana Pendidikan, 2021)
The experiment was carried out from May 2021 to August 2021 at Lahan Baru Universitas Singaperbangsa Karawang, Pasirjengkol Village, Majalaya District, Karawang Regency, West Java, The experiment method used in this study is an experimental method using a single factor Randomized Block Design (RAK), the number of treatments in this study consisted of 6 treatments repeated 4 times, the treatments consisted of : A (soil 100%), B ( soil 75% + Compost Paper 25%), C (Soil 75% + Rice Husk 25%), D (Soil 50% + Compost Paper 50%), E (Soil 50% + Rice Husk 50%), F (Soil 50% + Compost Paper 25% + Rice Husk 25%). The experimental results showed that the addition of compost waste paper mud and rice husks as a mixture of planting media gave significantly different effects on plant height 21 DAP and 28 DAP, number of leaves 21 DAP and 28 DAP, leaf area, root length, and fresh weight of red spinach. Treatment B, which was 75% soil + 25% paper compost, gave the highest yields for plant heights at 21 DAP and 28 DAP at 39.67 cm and 52.75 cm, the number of plant leaves at 21 DAP and 28 DAP at 28.00 strands and 46.50 strands, plant leaf area of ​​372.78 cm2, plant fresh weight of 78.56 grams, and treatment F namely 50% Soil + 25% Paper Compost + 25% Rice Husk gave the highest yield on the root length of red spinach of 43.95 cm.